(untitled) (Applied Biological Research, 2013)
An experiment was carried out in two consecutive rabi (winter) seasons of 2010 and 2011 on a silty clay loam soil to study the influence of four levels of farm yard manure FYM viz., 0, 15, 30 and 45 t ha-1and four levels of inorganic nitrogen viz., 0, 45, 90 and 135 kg ha-1on growth, yield attributes and quality of kale (Brassica oleracea L. var. acephala). Application of 45 t FYM ha-1 significantly increased growth and yield attributing characters of kale viz., plant height, plant spread, number of leaves, leaf yield plant-1, whole plant weight and leaf yield. Nitrogen @ 135 kg ha-1significantly increased all growth and yield parameters. The use of FYM @ 30 t ha-1in combination with 90 kg N ha-1 increased the growth and yield attributing characters of kale. The highest nitrogen uptake, nitrogen and protein content was recorded in kale under the treatment receiving 45 t FYM ha-1in combination with 135 kg N ha-1. Kale crop receiving 30 t FYM along with 90 kg N ha-1seemed to be the best combination in getting maximum growth and yield under temperate conditions of Kashmir.